THEORETICAL APPROACHES TO THE INTEGRATIVE DEVELOPMENT OF PROFESSIONAL COMPETENCE (SCIENCE TIME JOURNAL, 2026)
.The evolving prospect of education requires that the professional competence of the future language educators acquires a set of competencies. This article attempts to improve our comprehending of the nature of professional competence through integrative framework. It explores the theoretical foundations of the integrative professional competence development, including four main interconnected modules :motivational-value, pedagogical, activity-oriented, cognitive, and reflective-evaluative. Continuously, it offers several strategies for educators organizing project-based programs in order to integrate language, technology and methodology. The article aimed to demonstrate integrative development as a complex acquisition of discrete aspects, as well as combine language learning with extensive educational purposes.